Effects of β-Nicotinamide Mononucleotide, Berberine, and Cordycepin on Lipid Droplet Content and Developmental Ability of Vitrified Bovine Oocytes - Xi Xu; Baigao Yang; Hang Zhang; Xiaoyi Feng; Haisheng Hao; Weihua Du; Huabin Zhu; Adnan Khan; Muhammad Zahoor Khan; Peipei Zhang; Xueming Zhao (MDPI AG, 2023)
Oocyte vitrification is crucial for livestock reproduction, germplasm conservation, and human-assisted reproduction, but the overabundance of lipids is highly detrimental to oocyte development. It is necessary to reduce the lipid droplet content of oocytes before cryopreservation. This study analyzed the impact of β-nicotinamide mononucleotide (NMN), berberine (BER), or cordycepin (COR) on various aspects of bovine oocytes, including lipid droplet content and the expression levels of genes related to lipid synthesis in bovine oocytes, development ability, reactive oxygen species (ROS), apoptosis, and the expression levels of genes associated with endoplasmic reticulum (ER) stress, and mitochondrial function in vitrified bovine oocytes. The results of our study indicated that 1 μM NMN, 2.5 μM BER, and 1 μM COR were effective in reducing the lipid droplet content and suppressing the expression levels of genes involved in lipid synthesis in bovine oocytes. Our findings showed that the vitrified bovine oocytes treated with 1 μM of NMN had a significantly higher survival rate and better development ability compared to the other vitrified groups. Additionally, 1 μM NMN, 2.5 μM BER, and 1 μM COR decreased the levels of ROS and apoptosis, decreased the mRNA expression levels of genes involved in ER stress and mitochondrial fission but increased the mRNA expression levels of genes associated with mitochondrial fusion in the vitrified bovine oocytes. Our study results suggested that 1 μM NMN, 2.5 μM BER, and 1 μM COR effectively decreased the lipid droplet content and enhanced the development ability of vitrified bovine oocytes by lowering ROS levels, reducing ER stress, regulating mitochondrial function, and inhibiting apoptosis. Furthermore, the results showed that 1 μM NMN was more effective than 2.5 μM BER and 1 μM COR.